A Phase Ib Study of BEZ235, a Dual Inhibitor of Phosphatidylinositol 3‐Kinase (PI3K) and Mammalian Target of Rapamycin (mTOR), in Patients With Advanced Renal Cell Carcinoma. (10th June 2016) - Carlo, Maria I.; Molina, Ana M.; Lakhman, Yulia; Patil, Sujata; Woo, Kaitlin; DeLuca, John; Lee, Chung‐Han; Hsieh, James J.; Feldman, Darren R.; Motzer, Robert J.; Voss, Martin H.
Abstract : Lessons Learned: Our results highlight additional toxicities of dual PI3K/mTOR inhibition in the clinical setting that were unforeseen from preclinical models. Because of toxicity and lack of efficacy, BEZ235 should not be further developed in the current formulation for patients with renal cell carcinoma. Background: Allosteric inhibitors of the mammalian target of rapamycin complex 1 (mTORC1) are approved for advanced renal cell carcinoma (RCC). Preclinical models have suggested that dual inhibition of phosphatidylinositol 3‐kinase (PI3K) and mTOR kinase may establish superior anticancer effect. We aimed to establish safety for BEZ235, a potent inhibitor of both PI3K and mTOR, in advanced RCC. Methods: Patients with advanced RCC who had previously failed standard therapy received escalating doses of BEZ235 in sachet formulation twice daily until progression or unacceptable toxicity. Primary endpoints were to identify the maximally tolerated dose (MTD) and to determine the recommended dose for the phase II study. Results: The study was terminated early because of high incidence of dose‐limiting toxicities (DLTs) across all dose levels tested. Ten patients were treated with BEZ235—six with clear cell and four with non‐clear cell subtypes. Five of these patients suffered DLTs: 2 of 2 patients in the original 400 mg b.i.d. cohort, 1 of 6 in the 200 mg b.i.d. cohort, and 2 of 2 in the 300 mg b.i.d. cohort. DLTs included fatigue, rash, nausea and vomiting, diarrhea, mucositis, anorexia, and dysgeusia. Five patients were evaluable for response: Two had stable disease as best response, and three had progressive disease. Conclusion: BEZ235 twice daily resulted in significant toxicity without objective responses; further development of this compound will not be pursued in this disease.